The Patterns of Fiqh Thought of the Four Imams of the School of Islamic Jurisprudence and Their Implications for the Formation of Tolerant Character in the Digital Era - Adi Haryanto (Fusshilat : Jurnal Studi Pendidikan dan Keislaman, 2025)
This study aims to examine the characteristics of fiqh thought of the four major Islamic school imams and their implications for forming a tolerant character in the digital era. It employs a qualitative approach with library research, drawing on academic books, indexed journal articles, and relevant scholarly works on fiqh schools, ijtihad methods, and tolerance. Data were collected through systematic documentation with specific selection criteria and analyzed using the interactive model of Miles, Huberman, and Saldana, involving data condensation, display, and conclusion drawing based on thematic categorization. The findings reveal that differences among the four imams stem from variations in epistemology, ijtihad methods, and socio-historical contexts, reflecting the intellectual richness of Islamic tradition. These differences contain values that contribute to the development of tolerant character, manifested in attitudes such as accepting diversity, listening patiently, respecting differing opinions, avoiding hate speech, demonstrating humility, acting wisely, and fostering critical digital literacy communities. The study concludes that fiqh thought not only functions as a normative foundation of Islamic law but also holds contextual relevance in shaping tolerance in the digital age, requiring its actualization through analytical-contextual education and inclusive digital literacy.